2019
DOI: 10.22159/ijpps.2019v11i8.34040
|View full text |Cite
|
Sign up to set email alerts
|

Oleogels of Olive Oil and Soybean Oil for Topical Drug Delivery: A Comparative Analysis

Abstract: Objective: The objective of the present investigation was to develop olive and soybean oil-based oleogels with Span 40 and/or Tween 80 (as gelator and/or surfactant) and determine the critical gelator concentration (CGC), characterise and compare the rheological, thermal properties and drug release profile of the gels formed for topical delivery. Methods: Olive and soybean oil-based Span 40 and Span 40/Tween 80 oleogel formulations were prepared by solid fiber mechanism and subjected to organoleptic eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…A thermo cycling or freeze-thaw cycling method involves incubation of the freshly prepared oleogels at 65 • C for 15 min until they are a liquid, followed by gelation when the time was noted and another incubation at 4 • C for 15 min after which it is stored at 25 • C for 48 h. The cycle is repeated for 6 cycles. Soybean and olive oil-based oleogels structured with SPAN 40 or SPAN 40 and TWEEN 80 mixture were found to be stable up to 6 thermo-cycles [64], but an increase in the gelation time was observed after each cycle, for the olive oil oleogels structured with bot SPAN 40 or the mixture.…”
Section: Phase Transitionsmentioning
confidence: 96%
See 2 more Smart Citations
“…A thermo cycling or freeze-thaw cycling method involves incubation of the freshly prepared oleogels at 65 • C for 15 min until they are a liquid, followed by gelation when the time was noted and another incubation at 4 • C for 15 min after which it is stored at 25 • C for 48 h. The cycle is repeated for 6 cycles. Soybean and olive oil-based oleogels structured with SPAN 40 or SPAN 40 and TWEEN 80 mixture were found to be stable up to 6 thermo-cycles [64], but an increase in the gelation time was observed after each cycle, for the olive oil oleogels structured with bot SPAN 40 or the mixture.…”
Section: Phase Transitionsmentioning
confidence: 96%
“…Sorbitan esters (SPAN 40, 60, and SPAN 65) are low molecular weight gelators which have demonstrated structuring capacity; different concentrations (ranging between 15-20%) are needed in order to gel some edible oils for drug delivery purposes [55,64,102]. For instance, 17% Span 60 added to mustard oil will transform the system into an oleogel [55].…”
Section: Critical Gelationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the properties of oleogels vary significantly, which is dependent upon the molecular architecture of the oleogelator network [ 2 ]. Over the years, oleogels have been utilized in diverse fields ranging from food (e.g., preparation of cookies, cakes, chocolates, meat products, and ice-cream) and cosmetics to pharmaceutical industries (e.g., topical, ocular, and oral drug delivery systems) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. However, an incredible increment in the popularity and use of oleogel-based systems as novel drug delivery devices have been witnessed ever since.…”
Section: Introductionmentioning
confidence: 99%
“…The lipophilic nature of the oleogels assists the penetration of the drug molecules across the biological tissues [ 14 ]. Currently, oleogels have become an advanced approach for periodontal [ 14 ], nasal [ 15 ], topical [ 10 ], parenteral [ 16 ], and ocular [ 17 ] drug delivery applications. Unlike other fields, there has been a huge lack of research regarding the usage of oleogels for the controlled release of ocular therapeutics.…”
Section: Introductionmentioning
confidence: 99%